Ethnicity, nationalism and minority rights - May, Stephen, 1962-; Modood, Tariq; Squires, Judith; Cambridge eBooks (Cambridge : Cambridge University Press, 2004)
This interdisciplinary collection addresses the position of minorities in democratic societies, with a particular focus on minority rights and recognition. For the first time, it brings together leading international authorities on ethnicity, nationalism and minority rights from both social and political theory, with the specific aim of fostering further debate between the disciplines. In their introduction, the editors explore the ways in which politics and sociology can complement each other in unravelling the many contradictory aspects of complex phenomena. Topics addressed include the constructed nature of ethnicity, its relation to class and to 'new racism', different forms of nationalism, self determination and indigenous politics, the politics of recognition versus the politics of redistribution, and the re-emergence of cosmopolitanism. This book is essential reading for all those involved in the study of ethnicity, nationalism and minority rights.
Ethnicity, nationalism, and minority rights : charting the disciplinary debates / Stephen May, Tariq Modood, and Judith Squires -- Ethnicities and multiculturalisms : politics of boundaries / Jan Nederveen Pieterse -- Ethnicity without groups / Rogers Brubaker -- Ethnicity, class, and the 1999 Mauritian riots / Thomas Hylland Eriksen -- Black nationalism and African American ethnicity : the case of Afrocentrism as civil religion / Patricia Hill Collins -- New nationalisms and collective rights : the case of South Asia / T.K. Oommen -- Justice and security in the accommodation of minority nationalism / Will Kymlicka -- Two concepts of self-determination / Iris Marion Young -- Redistribution or recognition? A misguided debate / Bhikhu Parekh -- Borders, boundaries, and the politics of belonging / Nira Yuval-Davis -- Is it time to be postnational? / Craig Calhoun.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Ethnicity; Human rights; Minorities -- Civil rights; Indigenous peoples -- Civil rights; Nationalism; Self-determination, National; Electronic books